2006
DOI: 10.1152/ajpheart.00764.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of infarct-derived and control ovine cardiac myofibroblasts in culture: response to cytokines and natriuretic peptide receptor expression profiles

Abstract: This study investigated whether gene expression profiles of myofibroblasts derived from infarcted myocardium differ from normal cardiac fibroblasts. We compared the expression of cytoskeletal proteins in cultured ovine cardiac fibroblasts derived from infarcted (ID) and noninfarcted ovine myocardium (NID) and the levels of expression of the natriuretic peptide receptors (NPR)-A and NPR-B in response to treatment with transforming growth factor (TGF)-beta1 and/or platelet-derived growth factor (PDGF). Transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Fibroblasts are arguably the most important component of the “living scar” responsible for myocardial repair, infarct healing and scar formation [58]. Several studies have shown that specific phenotypic alterations in post-MI or failing fibroblasts are maintained in vitro through several passages [911]; thus, post-MI remodeled fibroblasts may be grown in culture to quantify alterations in intercellular communication and to study mechanisms underlying those alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts are arguably the most important component of the “living scar” responsible for myocardial repair, infarct healing and scar formation [58]. Several studies have shown that specific phenotypic alterations in post-MI or failing fibroblasts are maintained in vitro through several passages [911]; thus, post-MI remodeled fibroblasts may be grown in culture to quantify alterations in intercellular communication and to study mechanisms underlying those alterations.…”
Section: Introductionmentioning
confidence: 99%
“…The same study also showed an increase of platelet derived growth factor (PDGF) levels in response to tachypacing in fibroblasts isolated from atria but not ventricles. Similarly, another study by Jarvis et al20 using fibroblasts obtained from infarcted and non-infarcted ovine myocardium showed that the characteristics of cardiac fibroblasts in culture varied depending on the source. Their findings demonstrated lower levels of α-SMA, increased collagen I, higher expression levels of natriuretic peptide receptors (NPR-A and NPR-B) and differences in the response to TGF-β1 and PDGF treatment between cells obtained from infarcted and non-infarcted hearts.…”
Section: The Cardiac Myofibroblastmentioning
confidence: 84%
“…Fibroblasts are phenotypically heterogeneous depending on developmental stage, organ and physiological conditions 1420. In the heart, atrial and ventricular fibroblasts have different cell densities in intact tissue 17.…”
Section: The Cardiac Fibroblastmentioning
confidence: 99%
See 2 more Smart Citations